2020
DOI: 10.1002/gcc.22836
|View full text |Cite
|
Sign up to set email alerts
|

Novel ASAP1‐USP6, FAT1‐USP6, SAR1A‐USP6, and TNC‐USP6 fusions in primary aneurysmal bone cyst

Abstract: Aneurysmal bone cyst (ABC) is a benign but locally aggressive neoplasm, with a tendency for local recurrence. In contrast to other bone tumors with secondary cystic change, ABC is characterized by USP6 gene rearrangement. There is a growing list of known USP6 fusion partners, characterization of which has been enabled with the advent of next‐generation sequencing (NGS). The list of known fusion partners includes CDH11, CNBP, COL1A1, CTNNB1, EIF1, FOSL2, OMD, PAFAH1B1, RUNX2, SEC31A, SPARC, STAT3, THRAP3, and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Promoter swapping between USP6 and LUM, thus, took place with the expression of USP6 coming under the control of the LUM promoter leading to overexpression or ectopic activation of USP6. The pattern in the LUM-USP6 fusion gene was thus similar to that seen in previously reported USP6 fusion genes (6,(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Promoter swapping between USP6 and LUM, thus, took place with the expression of USP6 coming under the control of the LUM promoter leading to overexpression or ectopic activation of USP6. The pattern in the LUM-USP6 fusion gene was thus similar to that seen in previously reported USP6 fusion genes (6,(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 86%
“…In each translocation, the entire USP6 coding sequence was fused downstream with the promoter region of the partner gene: thyroid hormone receptor associated protein 3 (THRAP3 at 1p34), CCHC-type zinc finger nucleic acid binding protein (CNBP at 3q21), osteomodulin (OMD at 9q22), and collagen type I alpha 1 chain (COL1A1 at 17q21) (8). Additional studies have detected fusion of USP6 with the genes FOS like 2, AP-1 transcription factor subunit (t(2;17)(p23;p13)/FOSL2-USP6), catenin beta 1 (t(3;17)(p22;p13)/CTNNB1-USP6), SEC31 homolog A, COPII coat complex component (t(4;17)(q21;p13)/ SEC31A-USP6), FAT atypical cadherin 1 (t(4;17)(q35;p13)/ FAT1-USP6), secreted protein acidic and cysteine rich (t(5;17)(q33;p13)/SPARC-USP6), RUNX family transcription factor 2 (t(6;17)(p21;p13)/RUNX2-USP6), ArfGAP with SH3 domain, ankyrin repeat and PH domain 1 (t(8;17)(q24;p13)/ ASAP1-USP6), tenascin C (t(9;17)(q33;p13)/TNC-USP6), secretion associated Ras related GTPase 1A (t(10;17)(q22;p13)/ SAR1A-USP6), eukaryotic translation initiation factor 1 (t(17;17)(p13;q21)/EIF1-USP6), platelet activating factor acetylhydrolase 1b regulatory subunit 1 (t(17;17)(p13;p13)/ PAFAH1B1-USP6), signal transducer and activator of transcription 3 (t(17;17)(p13;q21)/STAT3-USP6), and ubiquitin specific peptidase 9 X-linked (t(X;17)(p11;p13)/USP9X-USP6) in other aneurysmal bone cysts (9)(10)(11)(12)(13). Thus, rearrangement of chromosome band 17p13 and the USP6 gene is now considered a characteristic genetic feature of aneurysmal bone cyst, with t(16;17)(q22;p13) as the most frequent chromosomal aberration found in 21% (9 out of 43) reported aneurysmal bone cysts with an abnormal karyotype (5,6,8,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…TNC has oncogenic properties through promotion of cell proliferation, migration and angiogenesis and its over-expression has been linked to a variety of malignancies [ 18 ]. Recently, fusions involving TNC have rarely been documented to occur in other neoplasms, including TNC-NRG1 fusion in a non-small cell lung carcinoma [ 19 ] and in a papillary renal cell carcinoma [ 20 ], and TNC-USP6 fusion in a primary aneurysmal bone cyst [ 21 ]. In these scenarios, TNC is functioned as a strong promoter, leading to activation of oncogenes NRG1 and USP6 , and subsequently induction of tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al [ 15 ] identified various rearrangements involving USP6 in 69% of primary ABCs and in none of the secondary ABCs, using fluorescence in situ hybridization (FISH). Using next generation sequencing, Guseva et al [ 18 ] and Sekoranja et al [ 19 ] increased the number of different gene rearrangements involving USP6 observed in primary ABCs to 100%.…”
Section: Introductionmentioning
confidence: 99%